O012 A prospective evaluation of the nature and time course of sleep disordered breathing and respiratory failure in patients with motor neurone disease (MND): the BreatheMND-1 study. (7th October 2021) - Aiyappan, V; Catcheside, P; Antic, N; Grivell, N; Hansen, C; Schultz, D; Graham, K; Allcroft, P; Glaetzer, K; McEvoy, D
Abstract: Introduction: Sleep disordered breathing (SDB) is a well-recognised but heterogeneous complication in MND and may herald the onset of respiratory failure. This study examined the nature and time course of SDB, sleep disruption and respiratory failure in MND patients. Methods: The BreatheMND-1 study recruited MND patients for prospective evaluation of muscle strength, supine and prone dyspnea, quality of life, pulmonary function, arterial blood gas and polysomnographic sleep measurements at baseline and, where possible, 3, 6 and 12 months for exploratory analyses. Results: 35 MND patients completed baseline and 25 at least one follow-up visit (median [IQR] follow-up time 8.7 [7.1–10.2] months). At baseline, patients were aged 64 [55–70] years, 16/35 (46%) female, with reduced FVC (77[59–92] %predicted) but relatively normal BMI (26.2[23.7–27.7] kg/m²) and PaCO2 (38.8[37.0–42.1] mmHg). At baseline and last follow-up, the prevalence of respiratory failure (PaCO2>45 mmHg or HCO3>27 mmol/l) was 9/33 (27%) and 12/27 (44%) respectively (p=0.186). Total sleep time and sleep efficiency were poor at baseline (5.2[4.6–5.9] h and 67.6[63.0–78.8]%) and declined at follow-up (by 1[0.3–1.9] h, p=0.020 and 7.9[-2.3–14.2]%, p=0.017 respectively). AHI was 7.2[2.8–14.6] /h and remained unchanged. In regression model, sleep time and efficiency were not predictive of respiratory failure, but the percentage of deep and REM sleep at last follow-up were (ROC area under curve 0.73±0.11, p=0.048 and 0.84±0.09, p=0.001). Discussion: Sleep quality in MND is remarkably poor, irrespective of SDB, and could reflect and/or impact MND progression. Thus, further strategies to monitor & improve sleep are clearly warranted in patients with MND.